2022
DOI: 10.1101/2022.09.09.507239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Your turn, my turn. Neural synchrony in mother-infant proto-conversation

Abstract: Even before infants utter their first words, they engage in highly coordinated vocal exchanges with their caregivers. During these so-called proto-conversations, caregiver-infant dyads use a presumably universal communication structure - turn-taking, which has been linked to favourable developmental outcomes. However, little is known about potential mechanisms involved in early turn-taking. Previous research pointed to interpersonal synchronisation of brain activity between adults and preschool-aged children d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…In a study of the interactions of 5-month-old infants and their mothers, Nguyen et al [39] also examined turn-taking behaviour in conjunction with fNIRS recording of interbrain synchrony. They found that turn-taking behaviour was related to the interpersonal brain synchrony in the interaction, and also to the infant's later vocabulary size at 24 months of age.…”
Section: Core Processes In Interactionmentioning
confidence: 99%
“…In a study of the interactions of 5-month-old infants and their mothers, Nguyen et al [39] also examined turn-taking behaviour in conjunction with fNIRS recording of interbrain synchrony. They found that turn-taking behaviour was related to the interpersonal brain synchrony in the interaction, and also to the infant's later vocabulary size at 24 months of age.…”
Section: Core Processes In Interactionmentioning
confidence: 99%
“…Mothers, being reliable informants, offer tailored information (Csibra & Gergely, 2009;Outters et al, 2020), aligning with children's interests (Ackermann et al, 2020(Ackermann et al, , 2023Madhavan & Mani, 2023). Maternal interactions foster neural synchrony, coordinating gestures and words, enhancing learning opportunities (Leong et al, 2017;Nguyen et al, 2022;Piazza et al, 2020). Children may therefore similarly attend to objects sampled by their mothers and themselves, yielding no differences across trials.…”
Section: Do Social Partners Shape Sampling Strategies and Learning Su...mentioning
confidence: 99%